VAT Notches, Voluntary Registration, and Bunching : Theory and UK Evidence - Liu, Li (IMF Working Papers; Working Paper ;, 2019)
Using administrative tax records for UK businesses, we document both bunching in annual turnover below the VAT registration threshold and persistent voluntary registration by almost half of the firms below the threshold. We develop a conceptual framework that can simultaneously explain these two apparently conflicting facts. The framework also predicts that higher intermediate input shares, lower product-market competition and a lower share of business to consumer (B2C) sales lead to voluntary registration. The predictions are exactly the opposite for bunching. We test the theory using linked VAT and corporation tax records from 2004-2014, finding empirical support for these predictions.